Inscribed Fibonacci Circle Fractal in a Circular Radiator for Ultra-Wideband Antenna Operation and Size Reduction - J. A. Tirado-Mendez; D. Martinez-Lara; H. Jardon-Aguilar; R. Flores-Leal; E. A. Andrade-Gonzalez (International Journal of Antennas and Propagation)
In this article, a Fibonacci circle fractal is inscribed into a circular radiator in order to provide ultra-wideband behavior as well as a 50% size reduction compared to a conventional circular monopole. The third iteration of the Fibonacci series allows the antenna to obtain a steady S11 parameter over the operation bandwidth, going from 2.7 GHz to 14 GHz, an average gain around 1 dB, with a quasi-omnidirectional radiation pattern and a group delay no bigger than 1 ns, suitable for short-pulsed communications.